High-throughput screening identified inherited genetic variations in the EGFR pathway contributing to skin toxicity of EGFR inhibitors. (September 2015) - Hasheminasab, Sayed-Mohammad; Tzvetkov, Mladen V; Schumann, Christian; Rüdiger, Stefan; Boeck, Stefan; Heinemann, Volker; Kächele, Volker; Steffens, Michael; Scholl, Catharina; Hichert, Vivien; Seufferlein, Thomas; Brockmöller, Jürgen; et al.
Aim: To identify genomic variants in the EGFR pathway and in cytokines predisposing to skin toxicity from EGFR inhibitors.Patients & methods: In 126 patients with cancer and EGFR inhibitor therapy skin toxicity was quantified and EGFR and inflammatory pathway genes were analyzed by deep sequencing.Results: We found 1437 SNPs in the 382-kb target region. Three SNPs in EGFR intron 1 were found exclusively in patients without skin rash. Another EGFR intron 23 SNP was associated with skin rash, overall survival and IL8 plasma concentrations. Moreover, carriers of the PIK3R1 326I variant were predisposed to skin rash and better survival.Conclusion: Comprehensive pathway-based resequencing revealed some new but only moderately strong genomic predictors of skin toxicity.